Perceived Social Support and Its Relationship with Self-esteem in Community-dwelling Older Adults - Mahdi Zolfaghari; Reza Hosseinabadi; Nasrin Galedar; Rasool Mohammadi (Mazandaran University of Medical Sciences, 2024)
Introduction and purpose: Self-esteem as a predictor of physical and mental health is affected by social factors. People in old age limit their relationships with family members and friends; nonetheless, it is not clear which members of the social network affect the self-esteem of people in old age. Therefore, the present study aimed to assess the relationship between perceived social support and self-esteem of the elderly residents of Khorramabad in 2023. Methods: In this descriptive-analytical study, 340 older adults aged 60 years and older in Khorramabad were selected via random cluster sampling method. Research data were collected using demographic information form, abbreviated mental test score, Zimet perceived social support questionnaire, and Rosenberg self-esteem questionnaire. The data were analyzed in SPSS software (version 22) using independent t-tests, ANOVA, Pearson's correlation coefficient, and linear regression. Results: The mean age score of participants was 69.51±7.55 years; 175 (51.5%) cases were female; and 235 (69.1%) subjects were married. The results of the study demonstrated that the variable of total social support, social support of family and friends, had a direct and significant relationship with self-esteem (P<0.001). In addition, there was a significant relationship between education and self-esteem (P<0.001). Conclusion: Perceived social support from family and friends plays a key role in older adults' self-esteem, especially the lonely ones. It is recommended that older adults and families protect and develop their family relationships and friendships to have better mental health.